Whiteness, repressive victimhood, and the foil of the intolerant left. Issue 1 (2nd January 2021) - Kelly, Casey Ryan
ABSTRACT: This essay argues that recent controversies over conservative speakers on college campuses are an opaque vehicle for White supremacy. Revisiting Herbert Marcuse's concept of repressive tolerance through the lens of Critical Race Theory, this essay sketches the features of repressive victimhood : the advancement of categorical minority status orchestrated to shield white people from charges of intolerance while reframing counterspeech as commensurate with overt bigotry.